The Routledge companion to contemporary anthropology
1 online resource (546 pages)
Keywords: The Routledge Companion to Contemporary Anthropology is an invaluable guide and major reference source for students and scholars alike, introducing its readers to key contemporary perspectives and approaches within the field. Written by an experienced international team of contributors, with an interdisciplinary range of essays, this collection provides a powerful overview of the transformations currently affecting anthropology. The volume both addresses the concerns of the discipline and comments on its construction through texts, classroom interactions, engagements with various publics, and changing relations with other academic subjects. Persuasively demonstrating that a number of key contemporary issues can be usefully analyzed through an anthropological lens, the contributors cover important topics such as globalization, law and politics, collaborative archaeology, economics, religion, citizenship and community, health, and the environment. The Routledge Companion to Contemporary Anthropology is a fascinating examination of this lively and constantly evolving discipline.